Investigation of attention deficit and hyperactivity disorder in adult patients with atopic dermatitis - Cicek, Demet; Kandi, Basak; Dertlioglu, Selma Bakar; Gunay, Sennur; Halisdemir, Nurhan; Turgay, Atilla; Colak, Cemil (Taylor & Francis Ltd, 2009)
Background. Atopic dermatitis (AD) is a common chronic inflammatory disease that is associated with significant psychosocial morbidity and a decrease in health-related quality of life. Attention deficit hyperactivity disorder may be present in atopic dermatitis patients. Objective. The present study aims to investigate the co-presence of ADHD in adult patients with AD. Material and method. The study registered 60 adult patients with AD (48 females and 12 males) and 50 non-atopic control subjects (38 females and 12 males). The AD patient group and the control group were assessed using the Turgay adult Attention-Deficit/Hyperactivity Disorder (ADD/ADHD) DSM-IV-Based Diagnostic Screening and Rating Scale (Turkish Version), which was studied by a team of psychologists and psychiatrists in Turkey for validity, reliability and norms. The scale covers three dimensions of the disease, namely inattention, hyperactivity and impulsivity, and associated features of ADHD. The groups were compared and contrasted in terms of their similarities and differences in ADD/ADHD symptoms. Results. Three sub-dimensions of ADD/ADHD scale (Attention Deficit, Hyperactivity/Impulsivity and Problem subdivisions) in AD patients were found statistically significantly elevated relative to controls (P<0.001, P<0.001, P<0.001, respectively). Conclusions. In conclusion we established the co-presence of ADHD in AD patients in the adult age group.
Keywords: Atopic dermatitis; attention-deficit; hyperactivity disorder